Copper-Catalyzed Synthesis of N-Aryl and N-Sulfonyl Indoles from 2-Vinylanilines with O2 as Terminal Oxidant and TEMPO as Cocatalyst - Liwosz, Timothy W.; Chemler, Sherry R. (Synlett, 2015)
A copper-catalyzed intramolecular alkene oxidative amination that utilizes TEMPO as cocatalyst and O2 as the terminal oxidant has been developed. The method furnishes N-aryl and N-sulfonyl indoles from N-aryl and N-sulfonyl 2-vinylanilines, respectively. Additionally, sequential copper-catalyzed reactions where initial Chan–Lam coupling of 2-vinylanilines with arylboronic acids is followed by oxidative amination of the alkene can generate N-aryl indoles in one pot.
Keywords: copper; oxidation; indoles; oxygen; TEMPO